The Implementation of Bantu Warga Apps and Metabase for Spatial Data Processing In Surabaya - Alfandino rasyid; Sritrusta Sukaridhoto; Muhammad Agus Zainuddin; Rizqi Putri Nourma Budiarti; Ubaidillah Zuhdi; Agus Imam Sonhaji; Yohanes Yohanie Fridelin Panduman; Luqmanul Hakim Iksan (Rekayasa, 2023)
Civil registration and vital statistics (CRVS) is known as an essential supporting system for effective policy-making and service delivery. Its primary purpose is establishing an individual's legal identity and vital events to ensure all citizens get their rights well. Furthermore, an advanced level of CRVS is equipped with a forecasting system to serve more useful data. This paper discusses the potential benefits and challenges of using Metabase and Bantu Warga as civil ministry support systems. The spatial data visualization system using open-source Metabase ran well and resulted in many visualization geospatial maps like birth, marriage and divorce, education, and employment. The forecasting autoregression model configuration and cumulative sum dataset reach the best error result in 1056618. The other aspects, like the self-isolation management system, civil documents classification system, and OCR system, have a good result.